Empowering Women through Non-Formal Creative Handicraft Education in Atauro Island - Valentina Tutu Paok; Harsuko Riniwati; Eti Setiawati (FOUNDAE (Foundation of Advanced Education), 2025)
Atauro Island has been highlighted in various studies that emphasize its ecotourism potential and natural beauty. However, very few studies specifically discuss women’s contributions to local development, especially through non-formal education that encourages creativity and economic empowerment through handicrafts. This study aims to analyze how the role of non-formal education in empowering women through the production of Boneca de Atauro handicrafts on Atauro Island, Timor-Leste. Using a qualitative approach and descriptive methods. There were 52 women who involved in this study. Data were collected through observation, in-depth interviews, and documentation. The results of the study indicate that amidst limited formal support from the government, women craftspeople are able to build economic and social capacity through community-based learning, intergenerational mentoring, and the use of local wisdom. This process not only strengthens cultural identity but also creates sustainable economic opportunities. This initiative also supports the achievement of the Sustainable Development Goals (SDGs), especially in the fields of education, gender equality, and local economic growth. This study confirms that non-formal education is a strategic pathway for grassroots-based development in remote areas.